Perlindungan Hukum Terhadap Pekerja dalam Terjadi Pemutusan Hubungan Kerja (PHK) Akibat Corporate Action di Tinjau dari Undang-undang No. 11 Tahun 2020 Tentang Cipta Kerja (Cluster Ketenagakerjaan) - Abdul Hadi; Dadan Herdiana (Rechtsregel : Jurnal Ilmu Hukum, 2021)
This research is motivated by the birth of Article 154A Paragraph (1) Letter a of Law no. 11 of 2020 concerning Job Creation (employment clusters). In this provision, it is explained that Termination of Employment can occur because the company merges, consolidates, takes over or separates the companies and the worker/laborer is not willing to continue the working relationship or the entrepreneur is no longer willing to accept the worker/labourer. However, layoffs due to the occurrence of this Corporate Action in practice are not always as expected, where workers/labourers who are not willing to continue working relationships due to merger, consolidation, takeover or separation of companies are considered to have resigned voluntarily which could have an impact on normative rights. workers/laborers when laid off. This study raises 2 (two) problems related to layoffs due to Corporate Action, namely first, how is the Corporate Action mechanism in the case of companies merging, consolidating, taking over, or separating companies. Second, what are the normative rights of workers/labourers that should be accepted in the event of layoffs due to Corporate Action. This study aims to find an appropriate Corporate Action mechanism when the company merges, consolidates, takes over, or separates companies, so that it can provide fair legal protection for both workers/labourers and employers. This study uses a qualitative research method with a normative juridical approach, where the data collected to answer the problem formulation is taken based on a literature study that is guided by laws and regulations, books, literatures, articles or journals. journals and other materials related to the issues discussed. After the data has been collected, the writer then analyzes it using the prescriptive analysis method, which is an analysis method based on the data collected to obtain clues which in the end draws a conclusion. The results of this study indicate that Article 154 A of Law no. 11 of 2020 concerning Job Creation states that employers can lay off workers if there is a Corporate Action. The use of the word "can" has the meaning that the provision is non-coercive. So doing or not terminating the employment relationship in the event of a Corporate Action is the entrepreneur's constitutional right which is regulated by law. Although layoffs due to this corporate action are the prerogative of employers, in its implementation, layoffs cannot be carried out but must comply with the procedures for termination of employment. Where in the event of a layoff, the entrepreneur is obliged to pay severance pay and/or gratuity for the period of service and/or compensation for entitlements that should be received by the worker.